Green Hotels Current Scenario and Future In India: a Conceptual Framework: Sustainable Practices in the Hotel Industry (Journal of Advances and Scholarly Researches in Allied Education, 2013)
This conceptual paperfocuses on the current scenario and the future of green hotels in India. Greenhotels also known as Eco hotels are accommodation or hotel which are ecowelcoming. For last few decades, green practices have been commonly embraced byhotels. Hotels are constantly becoming greener and environment friendly byadopting the green practices such as energy conservation, waste materialmanagement, water management, green building concept, etc. From the study it isrevealed that the hotels are working more on the training part of the employeesso that they must follow the green practices. The hotels will come up with thebig change in the world of business by adopting the Green Marketing becausegreen marketing is essential to save world from pollution.